Students’ Perceptions Of The Quizizz application In Learning Grammar - Bahri, Ahmad Saiful; Mardiana, Wiwik; Saifulloh, Ahmad Iklil (Philosophiamundi, 2024)
This research aims to explore student perceptions on the Quizizz application for learning grammar in the English Club at UNIM. This experimental study employs an in-depth interview design using a qualitative approach, with a population of 2 students selected through saturated sampling. Data were collected using interviews and documentation. The results of the study indicate that: In the experimental testing using the Quizizz Teaching media, student learning outcomes in grammar showed positive responses after applying the Quizizz Teaching media. Students who achieved the highest ranks responded positively to the Quizizz application. Based on the analysis using pre-tests and post-tests, there was an increase in student interest in learning grammar. From the results of this research, it can be concluded that the use of the Quizizz application positively affects the learning outcomes of students in the English Club at the Islamic University of Majapahit.